Geschiedschrijving en oorlogvoering. De metamorfose van een klassiek thema - Duindam, J. (BMGN - Low Countries Historical Review, 2003)
Jeroen Duindam, Historians and war: the metamorphosis of a traditional theme. This introduction describes the cold relationship between most academic historians and the field of military history. It argues that historians can no longer leave aside military history in considering the history of the state in Europe, European expansion, and a variety of other social and cultural themes. Special attention is given to the emergence of a social history of warfare and armies, and to the military revolution debate. Finally, a discussion of the exceptional position of the Low Countries as a ’school of war’ puts into perspective the other contributions to this volume. This article is part of the special issue ’Legerorganisatie en oorlogvoering in de Lage Landen tijdens de zestiende en zeventiende eeuw’.